THE EFFECT OF LEARNING MOTIVATION, PEERS, AND ADVERSITY QUOTIENT ON SELF-REGULATED LEARNING - Baagil, Khodijah; Susanti, Santi; Indriani, Susi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
Self-regulated learning is an important aspect that students must have in their learning activities. However, in actual learning situations Students frequently struggle to maintain their self-regulated learning when they encounter obstacles in their learning activities. This research aims to identify the effect of learning motivation, peers and adversity quotient on students self-regulated learning. This research method is quantitative research. The population used in this research are students in grade XI of the Accounting and Finance Expertise Program of Public Vocational High Schools in East Jakarta. Used Proportional Random Sampling Methods, in order that 140 respondents were obtained. Research data are processed using SPSS software. The research outcome shows that learning motivation has a significant effect on self-regulated learning, peers has a significant effect on self-regulated learning, adversity quotient has a significant effect on self-regulated learning, lastly learning motivation, peers, and adversity quotient simultaneously have a significant effect on self-regulated learning.